Zorro gets an outfit - Goodrich, Carter. (Simon & Schuster Books for Young Readers, 2012)
Zorro is embarrassed at having to wear a fancy outfit to the park and Mister Bud is unable to cheer him up until a "cool" new dog arrives in his own fancy clothes and challenges the friends to a race.